Development of the Physics Knowledge Enrichment Book “Lightning” to Improve High School Students’ Science Literacy and Environmental Literacy - Febriya, Dhea; Desnita, Desnita; Ratnawulan, Ratnawulan (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
The independent curriculum emphasizes literacy skills as the most important learning objectives. The two literacies that are greatly needed in the 21st century are science literacy and environmental literacy. However, these two literacies among high school students in Indonesia are still relatively low. The subject that is able to achieve both literacies in an integrated manner is physics. The purpose of this development research is to produce a physics knowledge enrichment book "lightning" to improve science literacy and environmental literacy of high school students that is valid and practical. This type of research is research and development (R&D) with the ADDIE model. The subjects of the study were physics teachers and grade XI high school students. Data were collected through questionnaires. Data analysis techniques include calculating the average score and Aiken validity index. The results of the study showed that: 1) The enrichment book was stated in the valid category in terms of material, language, presentation, and graphics; 2) The enrichment book by teachers and students was stated in the practical category in terms of ease of use, learning effectiveness, and benefits. Therefore, the physics knowledge enrichment book "lightning" that was developed is valid and practical as a solution to improve science literacy and environmental literacy of high school students.